Women's Empowerment in Digital Promotion Strategies for Optimization of Ecotourism Border Areas - Ayustia, Rissa; Nadapdap, Jones Parlindungan; Hosea, Hosea (International Conference on Sciences Development and Technology, 2022)
This study discusses the women empowerment in digital promotion strategies to solve the problem optimization of ecotourism border areas. This study uses a descriptive research method with a qualitative approach. The data collection technique used is the technique of Observation, Interview and Documentation. The research location is in Sebente Village, Shout District, Bengkayang Regency, West Kalimantan Province. The research subjects were the Sebente Village Head, Pokdarwis Chair, PKK Chairmen and members, women who had businesses, and visitors. The results showed that the optimization of ecotourism was carried out by empowering women in tourist villages through local potential and wisdom. This potential is the development capital of the village government so that women can have the ability to manage natural resources to increase production capacity, output, and ultimately improve women's welfare.